2017
DOI: 10.1080/15476286.2017.1391438
|View full text |Cite
|
Sign up to set email alerts
|

Distinct transcriptional and processing regulations control miR167a level in tomato during stress

Abstract: Besides their definite role in plant developmental processes miR167 also serve as mediator of stress response. Although differential expression of miR167 occurs during stresses, the regulatory-mechanism of biogenesis remained elusive. Therefore, using tomato as the model plant we have explored the mechanism of regulation of miR167a expression during stresses. Fungus or virus infections and exposure to cold stress raised the level of miR167a expression. Whereas, salt, drought and heat treatments resulted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The role of BLIL1-miR167 pair in response to mannitol stress. As miR167 was reported to be involved in stress responses 41 , we validated the competitive relationship among BLIL1, ARF6/8 and miR167 under www.nature.com/scientificreports www.nature.com/scientificreports/ osmotic stresses. We performed qRT-PCRs to examine the induction profile of BLIL1, ARF6/8 and miR167 under 200 mM mannitol stress.…”
Section: Identification Of the Cerna Pairs In Arabidopsis Seedlings Umentioning
confidence: 72%
“…The role of BLIL1-miR167 pair in response to mannitol stress. As miR167 was reported to be involved in stress responses 41 , we validated the competitive relationship among BLIL1, ARF6/8 and miR167 under www.nature.com/scientificreports www.nature.com/scientificreports/ osmotic stresses. We performed qRT-PCRs to examine the induction profile of BLIL1, ARF6/8 and miR167 under 200 mM mannitol stress.…”
Section: Identification Of the Cerna Pairs In Arabidopsis Seedlings Umentioning
confidence: 72%
“…Recent studies evidenced a critical function for 7 miR166 in tolerance to abiotic stresses in maize (Li et al, 2020) and cadmium-induced 8 toxicity in rice (Ding et al, 2018). By means of transgenic approaches it was established 9 that miR167 acts as transcriptional regulator in response to bacterial infection (Jodder, Basak, Das & Kundu, 2017) and temperature-induced stress in tomato plants (Jodder et al, 2018). Multiple evidences obtained by both sRNA-sequencing and transgenic approaches, support the role of members of the miR319-family, an ancient miRNA conserved across plant species ranging from mosses to higher plants, as a key modulator of the plant-environment interrelation (at biotic and abiotic level) in monocotyledonous and dicotyledonous species (Bustamante et al, 2018;Liu et al, 2019;Shi et al, 2019;Wu, Qi, Meng & Jin, 2020;Fang et al, 2021;Joshi, Chauhan & Das, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous works showed that GRSPaV reduce the levels of miR167 in infected plants 12 . MiR167 have been described to negatively regulate several genes associated with stress and development 33 . ARF6 and ARF8 are two target genes of miR167, both genes are necessary for the right floral development in several plants, such as Arabidopsis thaliana 34 , tomato 35 and soybean 36 .…”
Section: Discussionmentioning
confidence: 99%